Factors related to the capital structure of small new ventures. (1st January 2012) - Harms, Rainer; Breitenecker, Robert J.; Schwarz, Erich J.; Wdowiak, Malgorzata A.
N the literature, there exists evidence on the capital structure determinants for small ventures, but empirical research for new ventures is limited. We seek to address this gap by presenting a confirmatory analysis of determinants of capital structure of a sample of small new ventures in Austria. An understanding of the determinants of capital structure is vital since a lack of equity can have serious implications for the existence and the prosperity of a new firm. Indicators that relate to the human capital of the founder are easily available and are most prominent in venture financing decisions. Also, the industry chosen and growth intentions can serve as valuable indicators for external investors. Applying ordered logistic regression, influences of the education level, founding experience, leadership experience and turnover on leverage could be detected.